The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1182/blood-2014-10-605261
|View full text |Cite
|
Sign up to set email alerts
|

NOX2 is critical for heterotypic neutrophil-platelet interactions during vascular inflammation

Abstract: Key Points• NOX2-generated ROS regulate the function of surface receptors required for platelet-neutrophil interactions during vascular inflammation.Platelet-leukocyte interactions on activated endothelial cells play an important role during microvascular occlusion under oxidative stress conditions. However, it remains poorly understood how neutrophil-platelet interactions are regulated during vascular inflammation. By using intravital microscopy with mice lacking nicotinamide adenine dinucleotide phosphate (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 48 publications
3
81
0
1
Order By: Relevance
“…The development of in vivo imaging techniques, such as intravital microscopy (IVM) further allows to track cells in live animals over longer time periods in organs including cremaster muscle, liver, lung, brain and kidney (Figure 1C) (56,57), and have been greatly beneficial in analysing dynamic interaction between platelets and leukocytes (e.g. duration of interactions and behavioural changes in leukocytes and/or platelets upon contact) (10,53,55,5861). …”
Section: Methods To Measure Plasmentioning
confidence: 99%
See 3 more Smart Citations
“…The development of in vivo imaging techniques, such as intravital microscopy (IVM) further allows to track cells in live animals over longer time periods in organs including cremaster muscle, liver, lung, brain and kidney (Figure 1C) (56,57), and have been greatly beneficial in analysing dynamic interaction between platelets and leukocytes (e.g. duration of interactions and behavioural changes in leukocytes and/or platelets upon contact) (10,53,55,5861). …”
Section: Methods To Measure Plasmentioning
confidence: 99%
“…In this context, several markers specifically label platelets, including CD41 (GPIIb) (60), CD42 (GPIb) (61) and CD49b (α2 integrin subunit) (10,59,60,65). While the use of antibodies against these proteins enables clear identification of platelets interacting with other cells, some antibodies affect platelet function under certain conditions.…”
Section: Methods To Measure Plasmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12] Among several receptors and counter-receptors, the neutrophil-platelet association is primarily mediated by the interaction of neutrophil P-selectin glycoprotein ligand-1 (PSGL-1) and αMb2 integrin with platelet Pselectin and glycoprotein Ibα (GPIbα), respectively. 13 We have shown that AKT2 positively regulates the function of αMb2 integrin and P-selectin during vascular inflammation 12 and that combining hydroxyurea with AKT2 inhibition has immediate benefits in acute vaso-occlusive events and improves survival in SCD mice.…”
Section: Introductionmentioning
confidence: 99%